The Influence of Health Education About Breast Feeding On The Motivation of Breastfeeding Mothers - Pratiwi, Fitri Dwi (Health Gate, 2023)
Breastfeeding is a way of giving food to babies. Achieving breastfeeding requires strong knowledge and motivation from a mother. Mothers who know and understand the benefits they will receive if they are breastfed can encourage motivation. While in the hospital, health education about breastfeeding is needed to meet the information needs of mothers. Health education that is less than optimal in hospitals has an effect on the motivation of breastfeeding mothers. The purpose of this study was to analyze the differences in mothers' motivation in breastfeeding after being given health education about breastfeeding in the treatment group and the control group at Aminah Hospital Blitar. The research design was a quasi-experimental study with a pre-post test approach with control group design with a study population of 80-90 new mothers. Sampling by purposive sampling, 10 people in the control group and 10 in the treatment group. Data collection was carried out using a questionnaire that was carried out before and after the provision of health education. Data were analyzed using the Mann Whitney. The results showed that there were differences in the motivation of mothers in breastfeeding after being given health education about breastfeeding in the treatment group and the control group (p value= 0.004). Based on the research results, the provision of health education about breastfeeding has an effect on the motivation of mothers in breastfeeding. So it is suggested that the provision of health education about breastfeeding should be increased in order to achieve exclusive breastfeeding behavior